Ethno-Career Guidance: An Ethnographic Study of Career Guidance Based on Indigenous Baduy - Ramdhani, Rina Nurhudi; Nadhirah, Nadia Aulia; Hamzah, Rifqy Muhammad; Gofur, Ridwan (Bisma The Journal of Counseling, 2025)
Conventional Western-oriented career guidance models are not aligned with the value systems and practices of Indonesia's indigenous communities, creating significant gaps in service delivery. This research employs qualitative methodology with an ethnographic approach. This ethnographic study explores the career development practices of the community to develop a culturally sensitive career guidance framework. A qualitative ethnographic approach was employed within the community. Four key participants from communitywere purposively selected. Data were collected through participant observation and in-depth interviews using a validated interview guide with a reliability score of 0, 89. Thematic analysis was conducted using NVivo, with member validation, yielding an inter-coder reliability of over 85%. Six interconnected themes were identified: pagawean adat as cultural preservation; family influence in intergenerational knowledge transmission; wangsit and spirituality in career decisions; traditional educational systems; success concepts based on kasuksesan adat; tradition-modernity dilemmas. Baduy career development operates through a holistic cultural framework that integrates spirituality, communal responsibility, and environmental preservation, challenging individualistic Western models. There is an urgent need to decolonize career development theories and create guidance models grounded in indigenous values for culturally responsive practice.